Failed manual removal of the placenta after vaginal delivery - Bjurström, J; Collins, S; Langhoff-Roos, J; Sundberg, K; Jørgensen, A; Duvekot, J; Groenbeck, L; European Working group on Abnormally Invasive Placenta (Springer Berlin Heidelberg, 2017)
Purpose: A retained placenta after vaginal delivery where manual removal of placenta fails is a clinical challenge. We present six cases that illustrate the heterogeneity of the condition and discuss the etiology and terminology as well as the clinical management. Methods: Members of the European Working group on Abnormally Invasive Placenta (EW-AIP) were invited to report all recent cases of retained placenta that were not antenatally suspected to be abnormally adherent or invasive but could not be removed manually despite several attempts. Results: The six cases from Denmark, the Netherlands and the UK provide examples of various treatment strategies such as ultrasound-guided vaginal removal, removal of the placenta through a hysterotomy and just leaving the placenta in situ. The placentas were all retained but it was only possible to diagnose abnormal invasion in the one case, which had a histopathological diagnosis of increta. Based on these cases we present a flow chart to aid clinical management for future cases. Conclusion: We need properly defined stringent terminology for the different types of retained placenta, as well as improved tools to predict and diagnose both abnormally invasive and abnormally adherent placenta. Clinicians need to be aware of the options available to them when confronted by the rare case of a retained placenta that cannot be removed manually in a hemodynamically stable patient.